Preparation of Au-Ag Alloy Nanoparticles for Surface Enhanced Raman Scattering - Binh, Nguyen The; Dong, Nguyen Quang (VNU Journal of Science: Mathematics - Physics; Vol 31 No 1, 2015)
Using a laser-based method we study the preparation of Au-Ag alloy nanoparticles for Surface enhanced Raman scattering (SERS). Au and Ag nanoparticles (NPs) were prepared in distilled water by pulse laser ablation using 1064nm wavelength of Nd:YAG laser. Au-Ag alloy NPs were prepared by irradiating the mixture of colloidal Au and Ag NPs with the 532 nm second harmonic wavelength of Nd:YAG laser. The Au NPs, Ag NPs and Au-Ag alloy NPs were characterized by using UV-vis absorption spectroscopy, transmission electron microscopy (TEM) and X-ray diffraction measurements. The Au-Ag alloy NPs were used to fabricate nanostructure substrates for SERS measurement. Raman spectra were measured by a Micro-Raman spectrophotometer (LABRAM HR). Raman scattering enhancement by Plasmon excitation on Au-Ag alloy NPs were investigated. Keywords: Laser ablation, laser-induced synthesis, Au-Ag alloy nanoparticles, Surface enhanced Raman scattering (SERS).